SP2.2.5 Sarcopenia and lymphopenia in patients undergoing chemotherapy and surgery for oesophageal cancer. Can prehabilitive exercise be used to reverse the decline?. (9th August 2022) - Knight, William; Zylstra, Janine; Gervais-Andre, Louise; Goh, Vicky; White, Greg; Davies, Andrew
Abstract: Introduction: Studies have demonstrated that sarcopenia and lymphopenia are associated with poor oncological and survival outcomes in patients with oesophageal cancer. Neo-adjuvant chemotherapy (NAC) for oesophageal cancer is associated with muscle wasting and sarcopenic obesity. Lymphocytes are essential component of anti-tumour immunity. This study assesses the body composition and peripheral blood markers in patients undergoing a structured exercise program, during neo-adjuvant chemotherapy, as part of a non-randomised trial. Methods: A prospective non-randomised trial compared a standard care pathway to a structured prehabilitation exercise programme undertaken before and during NAC and surgery for oesophageal cancer. CT determined body composition analysis and peripheral blood markers were collected at multiple timepoints. Results: Comparison of the Intervention (n=21) and Control (n=19) showed Fat Free Mass increased during NAC in the intervention group (16.1 to 17.3 kg/m 2 ; control 15.4 vs. 14.8 kg/m 2, p =0.056) and Fat Mass Index to Fat Free Mass Index ratio (-5.51% Intervention, 10.74% control p=0.043) decreased in the treatment group. Lymphocyte subsets showed a marked increase in the intervention group after chemotherapy (CD3 10.92% vs 84.92% p=0.015, CD4 13.27% vs 107.75% p=0.0147, CD8 12% vs 69% p=0.033). Conclusion: A structured exercise programme prior to neoadjuvant chemotherapy reverses levels of sarcopenia, reduces visceral adiposity and increases levels of lymphocytes in patients with oesophageal cancer. Further studies will be needed to assess the oncological and clinical implications.